Computational simulation of a test facility in reduced scale for analysis of boron dispersion in a pressurizer of an integral compact and modular reactor (Brazilian Journal of Radiation Sciences (BJRS), 2021)
In an iPWR (integral pressurized water reactor), the pressurizer is located at the top of the reactor vessel; this configuration requires the investigation of the mechanisms adopted for the homogenization of boron. In previous work, three representative experiments were conducted in an experimental installation made of stainless steel with a volumetric scale equal to 1:200, representing one-fourth of the pressurizer of an iPWR. The test facility layout was mounted so that the test section was fed with water or saline solutions with different concentrations, representing scenarios of boration or deboration. To determine the concentration at the inlet and outlet of the test section, samples have been collected every 10 min during the experiments representing some scenarios. The main goal in this work was to investigate how well mixing during boron dilution transients in the pressurizer of a small modular reactor can be modelled accurately by CFD (Computational Fluid Dynamics) codes. Two CFD codes were used, the commercial ANSYS CFX and the open source CFD code OpenFOAM. The use of open source software such as OpenFOAM offers a way to CFD gain acceptance in the licensing. The results of the comparison of simulations with an experiment at the test section were presented and showed a very good agreement. It was verified that deviations are less than 4%, both codes can be used to accurately represent this phenomenon. In order to improve future experiments, the dispersion of the solution inside the test section is studied with the aim to propose positions for sensors. A first simple configuration is proposed, but some further simulations will be done to find an optimum configuration.